A new genus and family of copepods (Crustacea: Copepoda) parasitic on polychaetes of the genus Jasmineira Langerhans, 1880 (family Sabellidae) in the northeastern Atlantic - Boxshall, Geoff A.; O’reilly, Myles; Sikorski, Andrey; Summerfield, Rebecca (Zootaxa, 2015)
A new genus and species of copepod, Jasmineiricola mackiei n. gen. et n. sp., parasitic on at least three species of the sabellid polychaete genus Jasmineira Langerhans, 1880 is described. The adult female is mesoparasitic, living with part of its body (the endosoma) embedded within the host and part (the ectosoma) protruding through the host’s body wall. The endosoma consists of a well defined head region carried anteriorly on the trunk which has paired lateral lobes housing the ovaries. The head bears a rosette-like array of eight slender lobes, which are probably derived from the mouthparts. The only limbs present on the trunk are the subchelate maxillipeds positioned immediately posterior to the head. The ectosoma consists of a posterior genito-abdominal lobe bearing paired genital apertures. The male is unknown. The new genus cannot be placed in any of the five existing families of mesoparasitic copepods on polychaete hosts and is treated as the type of a new monotypic family, the Jasmineiricolidae. The new species occurs over a depth range from 19 to 279 m, and is widely distributed from UK coastal waters to Norwegian waters inside the Arctic Circle.